A support vector machine with the tabu search algorithm for freeway incident detection - Yao, Baozhen; Hu, Ping; Zhang, Mingheng; Jin, Maoqing (Zielona Góra: Uniwersytet Zielonogórski)
Automated Incident Detection (AID) is an important part of Advanced Traffic Management and Information Systems (ATMISs). An automated incident detection system can effectively provide information on an incident, which can help initiate the required measure to reduce the influence of the incident. To accurately detect incidents in expressways, a Support Vector Machine (SVM) is used in this paper.
Keywords: automated incident detection; support vector machines; tabu search; freeway